Child Rearing Practices among the Mamanuas of Pangaylan, Santiago, Agusan Del Norte - L. Bracamonte, Nimfa (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This is an ethnographic study conducted among the Mamanuas of Pangaylan in Agusan del Norte. More specifically, it investigated the training the child undergoes in the physical, emotional, and social areas and described its implications on the social and economic life of the Mamanua community. In general, the child rearing practices are characterized by permissive training in the physical area, strict training in the emotional area, except in aggression aspect, and good discipline in the social area.